Open bite in adult patients - Carlos Alberto Estevanell Tavares; Susiane Allgayer (Dental Press Editora, 2019)
ABSTRACT Anterior open bite (AOB) is characterized by the lack of overlap or contact between maxillary and mandibular incisors, while the posterior teeth are in occlusion. Correction of this malocclusion is challenging due to difficulties in determining and addressing the etiologic factors, and the high relapse rate. A multidisciplinary approach may be necessary, with participation of Orthodontics, Surgery and Speech Therapy, to achieve adequate esthetic and functional results for long term stability. The present paper discusses the treatment options for AOB, their advantages and implications.